Summertime plankton ecology in Fram Strait-a compilation of long- and short-term observations - Nöthig, Eva-Maria; Bracher, Astrid; Engel, Anja; Metfies, Katja; Niehoff, Barbara; Peeken, Ilka; Bauerfeind, Eduard; Cherkasheva, Alexandra; Gäbler-Schwarz, Steffi; Hardge, Kristin; Kilias, Estelle; Kraft, Angelina; et al. (Polar research, 2015)
Between Greenland and Spitsbergen, Fram Strait is a region where cold ice-covered Polar Water exits the Arctic Ocean with the East Greenland Current (EGC) and warm Atlantic Water enters the Arctic Ocean with the West Spitsbergen Current (WSC). In this compilation, we present two different data sets from plankton ecological observations in Fram Strait: (1) long-term measurements of satellite-derived (1998-2012) and in situ chlorophyll a (chl a) measurements (mainly summer cruises, 1991-2012) plus protist compositions (a station in WSC, eight summer cruises, 1998-2011); and (2) short-term measurements of a multidisciplinary approach that includes traditional plankton investigations, remote sensing, zooplankton, microbiological and molecular studies, and biogeochemical analyses carried out during two expeditions in June/July in the years 2010 and 2011. Both summer satellite-derived and in situ chl a concentrations showed slight trends towards higher values in the WSC since 1998 and 1991, respectively. In contrast, no trends were visible in the EGC. The protist composition in the WSC showed differences for the summer months: a dominance of diatoms was replaced by a dominance of Phaeocystis pouchetii and other small pico- and nanoplankton species. The observed differences in eastern Fram Strait were partially due to a warm anomaly in the WSC. Although changes associated with warmer water temperatures were observed, further long-term investigations are needed to distinguish between natural variability and climate change in Fram Strait. Results of two summer studies in 2010 and 2011 revealed the variability in plankton ecology in Fram Strait.